2017
DOI: 10.1126/science.aah4115
|View full text |Cite|
|
Sign up to set email alerts
|

Aging increases cell-to-cell transcriptional variability upon immune stimulation

Abstract: Aging is characterized by progressive loss of physiological and cellular functions, but the molecular basis of this decline remains unclear. We explored how aging impacts transcriptional dynamics using single-cell RNA-sequencing of unstimulated and stimulated naive and effector memory CD4 + T cells from young and old mice from two divergent species. In young animals, immunological activation drives a conserved transcriptomic switch resulting in tightly regulated gene expression, characterized by a strong up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
274
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(308 citation statements)
references
References 39 publications
21
274
0
Order By: Relevance
“…Recent advances in genomic sequencing and single cell technologies have enabled the detailed characterization of tumors at the single cell level (Macaulay et al, 2017). Although most of the single cell studies thus far have focused on defining individual cell types (Tirosh et al, 2016), single cell RNA-seq has also been used to characterize cell-to-cell variability in immune cells in aging (Martinez-Jimenez et al, 2017). Epigenetic regulators such as histone modifying enzymes are critical for the establishment of cell type-specific gene expression patterns, and thus, they are also likely to play a role in modulating cell-to-cell variability in transcription, but this has been mostly investigated in lower level organisms during aging (Booth and Brunet, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in genomic sequencing and single cell technologies have enabled the detailed characterization of tumors at the single cell level (Macaulay et al, 2017). Although most of the single cell studies thus far have focused on defining individual cell types (Tirosh et al, 2016), single cell RNA-seq has also been used to characterize cell-to-cell variability in immune cells in aging (Martinez-Jimenez et al, 2017). Epigenetic regulators such as histone modifying enzymes are critical for the establishment of cell type-specific gene expression patterns, and thus, they are also likely to play a role in modulating cell-to-cell variability in transcription, but this has been mostly investigated in lower level organisms during aging (Booth and Brunet, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although the presence of an inflammatory gene signature was associated with an improved vaccination response in young individuals, it was associated with a worse response in older individuals. There are many potential explanations for this observation, including differences in cell composition, cell activation state, the extent of chronic inflammation in older individuals, the possibility of intrinsic differences in vaccination responses of young and older adults, and the observed age-related change in transcriptional noise and cell-to-cell protein expression variation in immune cells (6163). The underlying reason for this inverse relationship is unclear and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Model organism aging studies have documented changes in global histone methylation patterns and, moreover, have established causal roles for the corresponding modifying enzymes in longevity (45, 89). Finally, a recent single-cell transcriptomic study found that T-cells from aging mice show a highly heterogeneous response to stimulation, consistent with increased epigenetic state variability or plasticity (90). …”
Section: Non-genetic Stimuli Of Plasticity or Restrictionmentioning
confidence: 92%